Poly(ADP-ribose)-dependent regulation of DNA repair by the chromatin remodeling enzyme ALC1. - Ahel, D; Horejsí, Z; Wiechens, N; Polo, SE; Garcia-Wilson, E; Ahel, I; Flynn, H; Skehel, M; West, S; Jackson, S; Owen-Hughes, T; Boulton, S (2009)
Posttranslational modifications play key roles in regulating chromatin plasticity. Although various chromatin-remodeling enzymes have been described that respond to specific histone modifications, little is known about the role of poly[adenosine 5'-diphosphate (ADP)-ribose] in chromatin remodeling. Here, we identify a chromatin-remodeling enzyme, ALC1 (Amplified in Liver Cancer 1, also known as CHD1L), that interacts with poly(ADP-ribose) and catalyzes PARP1-stimulated nucleosome sliding. Our results define ALC1 as a DNA damage-response protein whose role in this process is sustained by its association with known DNA repair factors and its rapid poly(ADP-ribose)-dependent recruitment to DNA damage sites. Furthermore, we show that depletion or overexpression of ALC1 results in sensitivity to DNA-damaging agents. Collectively, these results provide new insights into the mechanisms by which poly(ADP-ribose) regulates DNA repair.